When mischief came to town - Nannestad, Katrina (Houghton Mifflin Harcourt, 2015)
In 1911, when orphaned ten-year-old Inge comes to live with her stern grandmother in a remote island village in Bornholm, Denmark, she ends up changing the climate of the town, bringing joy and laughter to her grandmother's life, and finding a new family for herself to help assuage her grief over losing her mother
Keywords: Orphans; Grandmothers; Behavior; Grief; Bornholm (Denmark); Denmark; Jugendbuch